Family carers and caring : what it's all about - Milne, Alisoun; Larkin, Mary (Emerald Publishing Limited, 2023)
Carers and caring are contemporary global issues of growing political and societal significance. Changing demographics in the UK and beyond, as well as policy drivers promoting community-based living, mean that the family is increasingly the site of care for relatives with long term support needs. Whilst there is a plethora of literature on carers it tends to be situated in separate subject areas. For the first time Family Carers and Caring brings together a range of material and evidence about carers from different sources presented in an accessible and yet academically informed way. Milne and Larkin help to make sense of the complexities of family carers and caring, carving a coherent path through the academic, policy, socio-political, and practice terrain. Family Carers and Caring is explicitly underpinned by principles of social justice and rights, focusing on how inequalities intersect with caring.
Keywords: Caregivers.; Families -- Social aspects.; Social Science -- Sociology / Marriage & Family.; Sociology: family & relationships.; elektronické knihy; electronic books